(untitled) (Architecture Image Studies, 2025)
The complexity of urban environments requires effective navigation to be ordered in spatial behaviour, especially in commercial heritage areas such as Tunjungan Street, which go through a high traffic flow. Signage system serve as a cognitive elements that help the oriented and navigate a road users, but various form, design, and placement often effect in inconsistent navigation experiences. Yet there has been no comprehensive review examining the relation between signage characteristic, the visual perception, and behaviourof space users in the context of historic urban areas. This study uses a Systematic Literature Review of 10 selected articles to map the functions of signage, the visual cognition process, changes in public space behavior, and their implications for urban sustainability. The result shows that signage plays a role in enhancing the legibility of spatial information, reduce cognituive load and helped to guide movement patterns for both pedestriands and vehicles. This synthesis shows a knowledge gap regarding how signage functions as a spatial behavior controller in historic and high density areas to support the 11th point of SDGs. Therefore, prospect for future research is to focus on integrating signage design with mapping users cognitive load, also evaluating user behaviour to support safer, inclusive, and sustainable navigation.